Stachybotrys chartarum (atra) contamination of the indoor environment: Health implications - Bitnun, Ari (Pulsus Group Inc, 1999)
In 1998, widespread contamination of water-damaged school portables with the toxigenic mold Stachybotrys chartarum was detected in the province of Ontario. This mold may cause human disease through direct irritation, type 1 hypersensitivity or the production of toxins. A variety of respiratory, dermatological, eye and constitutional symptoms have been associated with heavy and prolonged exposure to S chartarum. S chartarum has also been potentially implicated as a rare cause of idiopathic pulmonary hemorrhage in infants. Ingestion of food heavily contaminated with toxin-producing molds, including S chartarum, can cause bone marrow suppression and immunotoxicity. However, the level of toxin exposure that occurs following inhalation of S chartarum is very low; consequently, serious adverse health effects from such an exposure are extremely unlikely. In a child with symptoms felt to be temporally related to the school environment, an assessment of the child’s school should be carried out by the public health authorities so that potential irritants and allergens can be identified. Avoidance of exposure is the most effective mode of therapy. Buildings found to be heavily contaminated with molds, particularly S chartarum, should undergo thorough cleaning and repair to remove the offending agent(s), and prevent further water damage and mold overgrowth.